SHORELINE CHANGE ANALYSIS WITH REMOTESENSING SENSED DATA IN THE HAU RIVER MOUTH AREA - Tien, Nguyen Ngoc; Cuong, Do Huy; Uu, Dinh Van; Sao, Nguyen Tho; Tuan, Tran Anh; Nam, Le Dinh (Vietnam Journal of Marine Science and Technology, 2018)
Multi-temporal Landsat data are used for this study over the period of 1989 to 2016 with imageries of 1989, 2001, 2009 and 2016. Band rationing method and threshold technique are applied for the coastline extraction. The Digital Shoreline Analysis System ENVI 5.1, eCognition and ArcGIS 10.3 are used to calculate shoreline rate-of-change statistics from multiple historical shoreline positions. The results show that shoreline change in the Hau river mouth area has a trend of deposition between 1989 and 2016 (27 years) with the accretion area ranging from 162.68 ha to 1,210.83 ha. Meanwhile, the erosion area only ranges from 0.002 ha to 183.53 ha. The results obtained from this study set a stage for new studies to understand the morphological changes of the river mouths in the Mekong Delta and coastal areas of Hau river.